Human papilloma virus E7 oncoprotein abrogates the p53-p21-DREAM pathway - Fischer, Martin (Sci Rep, 2017)
High risk human papilloma viruses cause several types of cancer. The HPV oncoproteins E6 and E7 are essential for oncogenic cell transformation. E6 mediates the degradation of the tumor suppressor p53, and E7 can form complexes with the retinoblastoma pRB tumor suppressor. Recently, it has been shown that HPV E7 can also interfere with the function of the DREAM transcriptional repressor complex. Disruption of DREAM-dependent transcriptional repression leads to untimely early expression of central cell cycle regulators. The p53-p21-DREAM pathway represents one important means of cell cycle checkpoint activation by p53. By activating this pathway, p53 can downregulate transcription of genes controlled by DREAM. Here, we present a genome-wide ranked list of genes deregulated by HPV E7 expression and relate it to datasets of cell cycle genes and DREAM targets. We find that DREAM targets are generally deregulated after E7 expression. Furthermore, our analysis shows that p53-dependent downregulation of DREAM targets is abrogated when HPV E7 is expressed. Thus, p53 checkpoint control is impaired by HPV E7 independently of E6. In summary, our analysis reveals that disruption of DREAM through the HPV E7 oncoprotein upregulates most, if not all, cell cycle genes and impairs p53’s control of cell cycle checkpoints.